Niobatos de potássio a partir de precursores sintetizados pelo método solvotermal assistido por micro-ondas - Duarte, Thiago Marinho (2014)
Potassium niobates are mixed oxides that can be applied to various photocatalytic processes. The synthesis of these materials by assisted microwave solvothermal method is proposed, considered impactful due to several factors. The literature contains little information on the employment this synthesis method to obtain potassium niobates. This study evaluates the influence of various synthesis parameters, such as reaction time, pH of the reaction medium, concentration of K+ in the composition of the synthesized material and implementing them in photodegradation tests Remazol Golden Yellow Dye. The powders were characterized by X-ray diffraction (XRD), infrared spectroscopy (IR), Raman spectroscopy, ultraviolet and visible spectroscopy (UV-Vis), surface area analysis by the BET method, thermogravimetric analysis (TG), and field emission scanning electronic microscopy (FE-SEM). The evaluation short and long range allows inferred through that the SMO method there was obtained two materials in pH function, the Lindquist salt (pH 14) and amorphous materials (pH 5 and pH 6). These materials when undergo to calcination temperatures of 650 °C lead to the formation of KNbO3 and two lamellar perovskite materials (KNb3O8 and K4Nb6O17) respectively . The powders obtained after calcination also were assessed as to their organization in the short and long range, and the results are in agreement with literature. The obtained semiconductors were tested as photocatalysts, and the results obtained show that the perovskite phase has no direct activity on the other hand, the lamellar niobates had satisfactory photocatalytic activity.